(untitled) (European Journal of Marketing and Economics, 2022)
Outsourcing has been a very commonly used strategy to increase productivity in a variety of organizations. In Mexico, it can be said that it has had a positive impact on employment rate. Nevertheless, there is a “dark side” in this strategy, since it has been used as a way to avoid direct hiring of employees and to evade fiscal and social security regulations. This document aims to analyze outsourcing from a regulatory and contractual approach, as well as its role as a way to increase the employment rate, and from a managerial perspective. As a result of this analysis, it was found that in our country outsourcing has been a successfully used strategy by many organizations of different sizes, but at the same time, the lack of an appropriate legislation has originated a series of unethical practices. In Mexico, in 2021 a new legal framework that tries to balance the relationship between firms and employees was approved. This paper ends with a reflection of the possible impacts of this new legislation.